THE IMPORTANCE OF ORGANIC FARMING IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS IN POLAND - Biernat-Jarka, Agnieszka; Trębska, Paulina (Acta Scientiarum Polonorum. Oeconomia, 2018)
Organic farming is one of the basic elements of constant and sustainable development of rural areas. It is the highest form of protection of the natural environment in the field of agriculture. The aim of the article is to present the development of organic farming in Poland, which became particularly important after joining the European Union. Poland strives to increase this type of production, the more so because it has considerable predispositions and favourable conditions. Organic farming in Poland shows quite large regional variations, resulting largely from natural conditions. The largest number of organic farms in 2016 occurred in the Warmińsko-Mazurskie and Podlaskie Voivodeships, and the smallest in the Opolskie and Śląskie Voivodships. The analysis uses data from the Central Statistical Office (GUS) and the Main Inspectorate of Agricultural and Food Quality (GIJHARS).